Subclinical Lipopolysaccharide from Salmonella Enteritidis Induces Dysregulation of Bioactive Substances from Selected Brain Sections and Glands of Neuroendocrine Axes - Anita Mikołajczyk; Dagmara Złotkowska (Toxins, 2019)
Bacterial lipopolysaccharide (LPS) can contribute to the pathogenesis and the clinical symptoms of many diseases such as cancer, mental disorders, neurodegenerative as well as metabolic diseases. The asymptomatic carrier state of Salmonella spp. is a very important public health problem. A subclinical single dose of LPS obtained from S. Enteritidis (5 μg/kg, i.v.) was administered to discern the consequences of changes of various brain peptides such as corticotropin-releasing hormone (CRH), gonadotropin-releasing hormone (GnRH), thyrotropin-releasing hormone (TRH), galanin (GAL), neuropeptide Y (NPY), somatostatin (SOM), substance P (SP), and vasoactive intestinal polypeptide (VIP) in selected clinically important brain sections and endocrine glands of the hypothalamic-pituitary-adrenal (HPA), -thyroid (HPT), -ovarian (HPO) axes. The study was conducted on ten immature crossbred female pigs. The brain peptides were extracted from the hypothalamus (medial basal hypothalamus, preoptic area, lateral hypothalamic area, mammillary bodies, and the stalk median eminence), and pituitary gland (adenohypophysis and neurohypophysis) sections and from the ovaries and adrenal and thyroid glands. There was no difference in health status between LPS and the control groups during the period of the experiment. Nevertheless, even a low single dose of LPS from S. Enteritidis that did not result in any clinical symptoms of disease induced dysregulation of various brain peptides, such as CRH, GnRH, TRH, GAL, NPY, SOM, SP, and VIP in selected brain sections of hypothalamus, pituitary gland and in the endocrine glands of the HPA, HPO, and HPT axes. In conclusion, the obtained results clearly show that subclinical LPS from S. Enteritidis can affect the brain chemistry structure and dysregulate bioactive substance from selected brain sections and glands of the neuroendocrine axes. The exact mechanisms by which LPS can influence major neuroendocrine axes are not fully understood and require further studies.